Mr. Chartwell : a novel - Hunt, Rebecca (New York : Dial Press, 2010)
Charismatic, dangerously seductive, Mr. Chartwell unites eminent statesman Winston Churchill at the end of his career and the vulnerable young London librarian Esther Hammerhans.Can they withstand Mr. Chartwell's strange, powerful charms and his stranglehold on their lives? Can they even explain who or what he is and why he has come to visit?
Originally published in the United Kingdom by Fig Tree, 2010.
Keywords: Churchill, Winston, -- 1874-1965 -- Fiction; Widows -- Fiction; Clerks -- Fiction; Psychological fiction; Fantasy fiction; Historical fiction